Skin sensitizing effects of sulfur mustard and other alkylating agents in accordance to OECD guidelines. (10th October 2019) - Steinritz, Dirk; Lang, Simon; Popp, Tanja; Siegert, Markus; Rothmiller, Simone; Kranawetvogl, Andreas; Schmidt, Annette; John, Harald; Gudermann, Thomas; Thiermann, Horst; Kehe, Kai
Highlights: skin sensitizing potential of SM and related alkylating agents was assessed in vitro . a, 2 out of 3 Sens-ITS" (integrated testing strategy) was conducted. OECD tests 442C, 442D and 442E were used for the ITS approach. Our results demonstrate that the chemicals can be categorized as a skin sensitizer. Finally, a tentative AOP for SM-induced skin sensitization is suggested. Abstract: Vesicants cause a multitude of cutaneous reactions like erythema, blisters and ulcerations. After exposure to sulfur mustard (SM) and related compounds, patients present dermal symptoms typically known for chemicals categorized as skin sensitizer ( e.g. hypersensitivity and flare-up phenomena). However, although some case reports led to the assumption that SM and other alkylating compounds represent sensitizers, a comprehensive investigation of SM-triggered immunological responses has not been conducted so far. Based on a well-structured system of in chemico and in vitro test methods, the Organization for Economic Co-operation and Development (OECD) established procedures to categorize agents on their skin sensitizing abilities. In this study, the skin sensitizing potential of SM and three related alkylating agents (AAs) was assessed following the OECD test guidelines. Besides SM, investigated AAs were chlorambucil (CHL), nitrogen mustard (HN3) and 2-chloroethyl ethyl sulfide (CEES). The methods are described in detail in the EURL ECVAM D ata B ase service on AL ternative M ethods to animal experimentation (DB-ALM). In accordance to OECD recommendations, skin sensitization is a pathophysiological process starting with a molecular initiating step and ending with the in vivo outcome of an allergic contact dermatitis. This concept is called adverse outcome pathway (AOP). An AOP links an adverse outcome to various key events which can be assayed by established in chemico and in vitro test methods. Positive outcome in two out of three key events indicates that the chemical can be categorized as a skin sensitizer. In this study, key event 1 "haptenation" (covalent modification of epidermal proteins), key event 2 "activation of epidermal keratinocytes" and key event 3 "activation of dendritic cells" were investigated. Covalent modification of epidermal proteins measured by using the DPRA-assay provided distinct positive results for all tested substances. Same outcome was seen in the KeratinoSens assay, investigating the activation of epidermal keratinocytes. The h-CLAT assay performed to determine the activation of dendritic cells provided positive results for SM and CEES but not for CHL and HN3. Altogether, following OECD requirements, our results suggest the classification of all investigated substances as skin sensitizers. Finally, a tentative AOP for SM-induced skin sensitization is suggested.